664 EXPLORING THE FEASIBILITY OF THE INTERRAI CHECK-UP FORM (SELF-REPORTED) IN OLDER PEOPLE LIVING WITH FRAILTY IN THE COMMUNITY. (8th March 2022) - Rajpara, M K; Wilson, C; Gordon, A L; Cowley, A
Abstract: Introduction: Identifying the holistic needs of community dwelling older people is an essential component of clinical care. Current assessment instruments are limited by a narrow medical view and varied language use, referring to identical clinical concepts in different ways. The interRAI family of assessments have been designed to integrate health information across multiple settings. The interRAI Check-Up (Self-Reported) was designed to support the management of older adults with multi-morbidities in the community setting but has not yet been widely tested in clinical practice in the United Kingdom. Objectives: To investigate the extent to which the self-reported interRAI Check-Up tool could be used to assess older patients within the NHS. Methods: Patients attending two outpatient clinics were recruited to complete the interRAI Check-Up which comprised of 109 items. Time taken for tool completion and prompts needed were recorded. Patient and individual item completion rates were calculated and assessed for floor or ceiling effects. Patient views on completing the tool were collected as field notes. Clinic staff completed a questionnaire exploring their views of the tool. Thematic analysis was carried out on patient and staff data. Results: From 43 patient participants, the median time for tool completion was 25 minutes. The median patient completion rate was 96.6% and item completion rate was 97.1%. Of 105 analysed items, 55 items showed a ceiling or floor effect. The tool was found to comprehensively cover holistic needs but its length and complexity of structure was found to be a barrier during busy clinical practice. Conclusion: The Self-reported interRAI Check-Up tool was found to be feasible for use in the outpatient setting. Further research into which patient groups and locations would benefit most is recommended as well as how to practically implement the assessment into clinical practice within the NHS.